Uji Kemampuan Pemangsaan Predator Eocanthecona furcellata Asal Riau pada Mangsa Ulat Api Setora nitens di Laboratorium - Muhammad Abdul Gani; Rusli Rustam; Herman Herman (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
Oil palm is a major agricultural product and a mainstay sector as a source of income for people in Riau Province. Oil palm cultivation is inseparable from the pest attack Setora nitens. Control measures generally use synthetic insecticides. There needs to be an alternative in the control caterpillar pests fire Setora niten such as using the predator Eocanthecona furcellata. The objectives of this research were to obtain the predation rate and predation power of the predator Eocanthecona furcellata from Riau in control caterpillar pests fire Setora nitens at oil palm cultivation. The research was conducted in the laboratory of Plant Pest, Faculty of Agriculture, Riau University. This study consisted of 5 treatments with 5 replications so obtained 25 experimental units were placed in a completely randomized design (CRD). The treatments were A: 1 male, B: 1 female, C: 1 pair, D: 2 pairs, and E: 3 pairs of predator Eocanthecona furcellata. The results showed that the duration of prey handling of one caterpillar larva fire Setora nitens by predator Eocanthecona furcellata occurred for 3.18-6.24 hours. The treatment of three pairs of imago predators Eocanthecona furcellata is the best treatment, with a faster rate of predation and can prey on 66.00% of caterpillar fire.